Peran Media Sosial Sebagai Strategi Pemasaran Produk Pada UKM Arni Kripik - Candra Agus Wahyudhi (Musamus University, Merauke Papua Indonesia., 2019)
The purpose of this research is to explore social media utilization as a marketing strategy for small and medium enterprises (SMES). Method: A qualitative approach with case studies is used as a research design. Researchers used an in-depth interview on the owner Arni chips as well as informant. The results showed that the marketing strategy through online social marketing media conducted by Arni chips through Facebook and Instagram showed Facebook social media has more influence on the increase The sale of Arni chips products. Because in addition to being a media that has been owned by most of the community, the Facebook media also has a feature that is easy and suitable for promotion.